2013
DOI: 10.1017/s0025100313000236
|View full text |Cite
|
Sign up to set email alerts
|

Negative intraoral pressure in German: Evidence from an exploratory study

Abstract: Phonemic clicks are geographically limited to the African continent, but non-phonemic clicks can also occur in languages spoken elsewhere. One of the phonetic peculiarities of clicks is that they involve negative intraoral pressure. The current study is a survey of instances of negative intraoral pressure excursions in German, a European language which is known to show instances of weak clicks in consonant sequences. Data of spontaneous speech in monologues and read passages from 14 female subjects are analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Articulatory measurements of speech in preparation show that the tip of the tongue together with the increased inhalation may cause click sounds [37]. Although a velaric airstream cannot be excluded, it is more likely that an inhalation gesture with a sudden and strong vertical downwards movement of the larynx combined with an increased glottal opening provides the necessary negative pressure [9].…”
Section: Figurementioning
confidence: 99%
“…Articulatory measurements of speech in preparation show that the tip of the tongue together with the increased inhalation may cause click sounds [37]. Although a velaric airstream cannot be excluded, it is more likely that an inhalation gesture with a sudden and strong vertical downwards movement of the larynx combined with an increased glottal opening provides the necessary negative pressure [9].…”
Section: Figurementioning
confidence: 99%
“…The jet flows are also influenced by the alphabet-specific oral-motor controls, such as the closing-opening lips in /B/, the teeth touching in /C/, and the tip of the tongue pushing against the alveolar ridge in /D/. Inversely, based on the oral flow dynamics, one can infer the inner oral-motor motions, such as lip opening, tongue-tip retraction, tongue-root advancement, jaw dropping, and larynx lowering, which can further vary in duration, amplitude, and sequence [ 49 ]. It is observed that schlieren imaging captures only the side view of the lip and jaw motions, not the movements of the teeth and tongue inside the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers note that it is sometimes hard to clearly determine a click's place of closure or the type of airstream used [2][3][4]21]. Ogden [4] mentions percussives as another category of click-like sounds in discourse.…”
Section: Phonetic Characteristics Of Clicksmentioning
confidence: 99%